A comparison of observed and perceived seasonal climate regimes in a rural socio-ecological system in the northeastern South Africa - Rusere, Farirai; Houngué, Nina Rholan; Mkuhlani, Siyabusa; Soropa, Gabriel; Hunter, Lori; Twine, Wayne; Samimi, Cyrus (Regional Environmental Change, 2026)
This study investigated perceptions of climate change among residents of 12 villages in Bushbuckridge, Mpumalanga, South Africa, through household surveys and focus group discussions. These perceptions were compared with climatic trends derived from Skukuza meteorological station data (1981–2023), focusing on summer seasonal temperature and rainfall patterns. The analysis of meteorological station data revealed significant increases in seasonal maximum temperatures, a marked decline in the number of wet days, and high interannual variability in total seasonal rainfall. While local perceptions aligned with recorded trends of rising temperatures, delayed onset of the rainy season, and more erratic rainfall patterns, discrepancies emerged regarding total rainfall amounts; participants perceived an overall decline, whereas meteorological data showed no statistically significant long-term trend in seasonal rainfall totals. These findings highlight the value of integrating local knowledge into climate change research. Local perceptions provide critical insights into micro-level climate impacts, such as changes in rainfall frequency and intensity, that may not be evident in observational data. Combining these perspectives with scientific measurements can enhance the design of culturally relevant and effective climate adaptation strategies. This approach fosters stronger community engagement and ensures that policies address both the observed and perceived impacts of climate change, thereby supporting more sustainable and inclusive responses at local and national scales.
Keywords: Climate Change; Rural socio-ecological system; Observed and perceived seasonal climate regimes